Improving through-plane thermal conductivity of PDMS-based composites using highly oriented carbon fibers bridged by Al2O3 particles - Huang, Ruoyu; Ding, Dongliang; Guo, Xiaoxiao; Liu, Changjiang; Li, Xinhua; Jiang, Gaoxiao; Zhang, Yufeng; Chen, Yanhui; Cai, Weiwei; Zhang, Xue-ao (Composites science and technology, 2022)
Efficient thermal interface materials (TIMs) are urgently needed for heat dissipation of high-power density electronics. In this study, vinyl polydimethylsiloxane (PDMS) composites with the spatial alignment of carbon fibers (CFs) bridged by Al2O3 particles were fabricated by the flow field. The through-plane thermal conductivity (TPTC) of the composites with 24 vol% CFs and 47 vol% Al2O3 loading reached 38.0 W m−1 K−1. The oriented CFs bridged by Al2O3 acted as the efficient through-plane thermal conductive network. Furthermore, the effects of shape factor (b/a), spatial angle (γ) of CFs, and CF loading (Vf) on the TPTC were quantitatively discussed by steady-state finite element simulation combined with micro-computed tomography and machine learning. The positive contribution of the increased Vf to TPTC was in competition with the negative contribution of b/a and γ, both of which increased with the increase of Vf. Moreover, b/a exerted more negative effects than γ. The PDMS composites demonstrated excellent thermal stability (Td = 407.5 °C, CTE = −55.3 × 10−6 K−1), low compress modulus (1.71 MPa), and hardness (47 (Shore C)), which made them potential candidates for TIMs. This work offers a feasible method to prepare TIMs on large scale and refreshes the thermal conduction mechanism of TIMs by introducing the influencing factors (b/a and γ). [Display omitted] •Efficient heat conduction paths were constructed by spatial alignment of CFs bridged by Al2O3.•The through-plane thermal conductivity of PDMS composites reached 38 W m−1 K−1.•The effect of spatial orientation angle of CFs on the thermal conduction property was revealed.•The PDMS composites with excellent comprehensive properties can be used as TIMs.